The independent risks and specific biomarker of breast cancer-related ischemic stroke. (1st February 2021) - Cheng, Xuemin; Qin, Qixiong; Lu, Lizhi; Chen, Chunyong; Wei, Yunfei; Wang, Dacheng; Li, Haihua; Li, Guohui; Liang, Hongbin; Li, Shengyu; Cheng, Daobin; Liang, Zhijian
Abstract: Aim: This retrospective study was designed to investigate the independent risks and specific biomarker for breast cancer-related ischemic stroke (BCRS). Methods: Clinical features and laboratory findings were compared between BCRS group and breast cancer group without stroke, and further multivariate analyses were performed to predict independent risks factors for BCRS patients. A receiver operator characteristic (ROC) curve analysis was configured to estimate the diagnostic efficacy of each independent risk and the product of these risks and to obtain the optimal cut-off value of diagnosis, which was termed the BCRS Index. Results: BCRS patients had elevated plasma D-dimer and CA153 levels and platelet-to-lymphocyte ratio (PLR), as well as more patients received endocrine therapy (all p ＜ 0.05). Moreover, multivariate analysis revealed that D-dimer levels (odds ratio [OR]: 1.002; 95% confidence interval [CI]: 1.001–1.003; p = 0.000), CA153 levels (OR: 1.005; 95% CI: 1.001–1.008; p = 0.007), PLR (OR: 1.010; 95% CI: 1.004–1.015; p = 0.001), and endocrine therapy (OR: 1.268; 95% CI: 1.087–1.479; p = 0.003) were identified as independent risks of BCRS. Furthermore, ROC analysis displayed that the product of risks had the best diagnostic efficacy, of which the area under the curve was 0.846 ± 0.28. The optimum cut-off point was 2.37 × 10 6 /mL, which was termed the BCRS Index with higher diagnostic accuracy and validity. Conclusions: Endocrine therapy, as well as elevated plasma D-dimer and CA153 levels and PLR values may be independent risks for BCRS. Furthermore, BCRS Index should be served as a novel specific biomarker for BCRS, which is useful to distinguish BCRS for clinicians.